2024
DOI: 10.3389/fimmu.2023.1227648
|View full text |Cite
|
Sign up to set email alerts
|

Impaired activation of plasmacytoid dendritic cells via toll-like receptor 7/9 and STING is mediated by melanoma-derived immunosuppressive cytokines and metabolic drift

Matilde Monti,
Giorgia Ferrari,
Valentina Grosso
et al.

Abstract: IntroductionPlasmacytoid dendritic cells (pDCs) infiltrate a large set of human cancers. Interferon alpha (IFN-α) produced by pDCs induces growth arrest and apoptosis in tumor cells and modulates innate and adaptive immune cells involved in anti-cancer immunity. Moreover, effector molecules exert tumor cell killing. However, the activation state and clinical relevance of pDCs infiltration in cancer is still largely controversial. In Primary Cutaneous Melanoma (PCM), pDCs density decreases over disease progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…Specifically, the synergy between these cytokines was accountable for the TLR7/9 signaling inhibition, including IRF7 downregulation, impairing the I-IFN production by pDCs [ 124 , 125 ]. Accordingly, our group proposed a TGF-β-mediated functional impairment of TLR/MyD88-dependent signaling in melanoma-associated pDCs through IRF7 downregulation [ 126 ]. Wnt5a is an immunosuppressive molecule identified in the melanoma TME affecting pDC function [ 127 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, the synergy between these cytokines was accountable for the TLR7/9 signaling inhibition, including IRF7 downregulation, impairing the I-IFN production by pDCs [ 124 , 125 ]. Accordingly, our group proposed a TGF-β-mediated functional impairment of TLR/MyD88-dependent signaling in melanoma-associated pDCs through IRF7 downregulation [ 126 ]. Wnt5a is an immunosuppressive molecule identified in the melanoma TME affecting pDC function [ 127 ].…”
Section: Introductionmentioning
confidence: 99%
“…As thoroughly described in the following section of this review, pDC functionality has been linked to glycolysis in order to provide the high energy demand for rapid I-IFN production [ 153 ]. Our group has demonstrated that IFN-α production by melanoma-exposed pDCs was hijacked and could derive from their metabolic drift [ 126 ] (Fig. 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations